Emodin Improves Juvenile Largemouth Bass (Micropterus salmoides) Liver Health Through Nrf2/NF-κB Pathway and Fat Metabolism: Growth Performance, Immune Response and Resistance Against Aeromonas veronii Infection - Zhenxin Zhao; Fei Zhao; Tianxun Luo; Zhou Zhou; Xianbo Zhang (Animals)
The experiment was aimed at examining the influence of adding emodin to feeds on the growth performance, liver immunity, and resistance against Aeromonas veronii infection among juvenile largemouth basses and other potential mechanisms. A total of 540 fish (45 ± 0.3 g) were randomly divided into 6 diets, including EM-0, EM-250, EM-500, EM-1000, EM-2000, and EM-4000 diets, in which 0, 250, 500, 1000, 2000, and 4000 mg kg−1 emodin was added. Following a 60-day feeding test, it demonstrated that the feed conversion ratio (FCR) of juveniles within the EM-500 and EM-1000 groups remarkably exceeded that of the EM-0 group. Subsequently, unlike those in EM-0 group, the fish in the EM-1000 group showed heightened hepatocyte count, induced hepatic lipolysis-associated expression of peroxisome proliferators-activated receptor α (PPARα) and acyl-coenzyme an oxidase (ACO), and reduced the hepatic triglyceride (TG) levels. Additionally, EM-1000 could up-regulate the expressions of nuclear factor erythroid 2-associated factor 2 (Nrf2) and heme oxygenase-1 (HO-1) in livers compared with controls and boost antioxidant enzymes activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT), along with a lower content of reactive oxygen species (ROS) and malondialdehyde (MDA). Meanwhile, the EM-1000 group increased anti-inflammatory cytokines of interleukin-10 (IL-10) while suppressing the interleukin-8 (IL-8) expression of pro-inflammatory cytokines in livers by contrast to controls. In the end, juvenile largemouth bass in the EM-1000 group showed a comparatively highest survival rate, whereas fish in the EM-2000 and EM-4000 groups exhibited a little higher mortality than that of the EM-0 group. To sum up, our study exposed that supplementing emodin with 1000 mg kg−1 in diet could enhance the hepatic antioxidant status and unspecific immunity to reinforce the protective effect on disease resistance, resulting in improving the growth performance in juvenile largemouth bass.